The little engine that could : an abridged edition - Piper, Watty; Long, Loren (New York : Philomel Books, 2015)
Although she is not very big, the Little Blue Engine agrees to try to pull a stranded train full of toys over the mountain.
On board pages.
Keywords: Children's stories